2016
DOI: 10.1590/s1806-92902016000500004
|View full text |Cite
|
Sign up to set email alerts
|

Using juniper berry ( Juniperus communis ) as a supplement in Japanese quail diets

Abstract: -The present study was conducted to determine the effects of supplemented juniper berry (Juniperus communis) on fattening performance and some carcass traits of quails. A total of 150 one-day-old Japanese quail chicks were randomly divided into five groups (one control and four treated groups) with three replicates. Four different juniper berry levels (0.5, 1, 1.5, and 2%) and a control treatment (0%) were added to the diet. Juniper berry supplementation to the diets initiated at the end of the 1st week and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…The interest of the Juniperus species is also at the nutritional/functional food level and some studies, including in vivo studies on this subject, have recently been published. Inci and colleagues [ 22 ] found that low supplementation levels of J. communis berry (0.5% and 1%) in Japanese quails ( Coturnix coturnix japonica ) diets have positive impacts on some body qualities, feed intake, and live weight. Juniperus species are also valuable in terms of their wood since it is a viable construction material classified as durable or even very durable, like J. communis case [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The interest of the Juniperus species is also at the nutritional/functional food level and some studies, including in vivo studies on this subject, have recently been published. Inci and colleagues [ 22 ] found that low supplementation levels of J. communis berry (0.5% and 1%) in Japanese quails ( Coturnix coturnix japonica ) diets have positive impacts on some body qualities, feed intake, and live weight. Juniperus species are also valuable in terms of their wood since it is a viable construction material classified as durable or even very durable, like J. communis case [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effective protection of farm animals from various pathogens is widely used in synthetic semisynthetic antimicrobials. But it also raises the risk of developing resistance against these exploitation pathogens (Bach Knudsen, 2001;Botsoglou et al, 2002;Inci et al, 2016;Inci et al, 2016a). One of these is antibiotics and has been used for years, especially as a growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only the amount of Ca (890.5 mg/kg) in KM berries is higher than that in AA (794.7 mg/kg). HungaryWhen the mean values of the results considered, KM and AA berries contain more K, Mg, Fe and Zn than AY berries and raisins Inci et al (2016). reported that Juniperus communis berries contained 61.2 g/kg K, 1.90 mg/kg Mg, 80.12 mg/kg Fe, 15.31 mg/kg Mn, 18.80 mg/kg Zn and 19.94 mg/kg Cu.…”
mentioning
confidence: 94%